Evaluation of fermented of Palm Kernel Meal by Saccharomyces cerevisiae in Tilapia Fed - Achmad Noerkhaerin Putra; Syamsul Fajri Hidayat; Mas Bayu Syamsunarno; Mustahal Mustahal; Dodi Hermawan; Muh. Herjayanto (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Palm kernel meal (PKM) is the potential of raw material for feed fish ingredient because it has good nutritional content and abundant availability in Indonesia. The study was conducted to evaluate of PKM fermented as feedstuffs as well as the effect on feed digestibility of tilapia. This research consisted of 2 trials: the the test of S. cerevisiae fermentation on PKM and digestibility test of PKM as feedstuffs. The first trial used a factorial randomized design consisting of 2 factors: S. cerevisiae dose (0; 0.9; 1.5%) and incubation time (0, 24, 48 hours) with 3 replications. The second trial used a completely randomized design consisting of 3 treatment of test feed, namely A: reference feed, B: reference feed + PKM, C: reference feed + PKM fermented and 4 replications. Fish (initial weight: 5.34 ± 0.14 g) were reared in an aquarium for 40 days with a recirculation system. The results showed that the fermented of 1.5% S. cerevisiae and time incubation for 24 hours recorded the lowest crude fiber content (8.86 ± 0.51%). The highest total digestibility value (P <0.05) was found in treatment A (45.36 ± 2.17%) and C (46.61 ± 2.36%) compared to treatment B (38.46 ± 1, 07%). The highest protein digestibility value significantly (P <0.05) was found in treatments A and C (72.89 ± 4.57%, 74.27±1.26%, respectively) than treatment B (58.70 ± 3.57%). Finally, it can be concluded that the fermentation of PKM by S. cerevisiae can be used as feedstuffs for tilapia feed.